Revisão dos Lekiini (Diptera, Tachinidae) neotropicais - Nunez, Enio (2005)
The Leskiini (Diptera : Tachinidae, Tachininae) is a cosmopolitan tribe found in all geographic regions. It comprises 49 genera throughout the world, 18 of them occurring in the neotropics: Beskioleskia Townsend, Galapagosia Curran, Genea Rondani, Geneodes Townsend, leskia Robineau-Desvoidy, Metamyobia Townsend, Mintholeskia Townsend, Parthenoleskia Townsend, Proleskiomima Townsend, Spathipalpus Rondani, Stomatodexia Brauer & Bergenstamm, Tapajoleskia Townsend, Tipuloleskia Townsend, Trichopyrrhosia Townsend, Trochiloglossa Townsend, Trochiloleskia Townsend, Uruleskia Townsend and Urumyobia Townsend. National and foreign collections were studied and type-material of almost all genera were examined. This revision of the neotropical Leskiini the taxonomic changes proposed resulted in 1O valid genera to this region: Genea Rondani; Leskia Robineau-Desvoidy; Proleskiomima Townsend; Spathipalpus Rondani; Stomatoderia Brauer & Bergenstamm; Tipuloleskia Townsend; Uruleskia Townsend; Eumyobia Townsend and Sipholeskia Townsend, (both included in Leskia Robineau-Desvoidy synonymy had their status revalidated) and Murya gen.nov. . The other genera received the following treatment: Beskioleskia, Mintholeskia and Trichopyrrhosia were transferred to Dexiinae subfamily based on their characteristic hinged distiphallus, the second one (Mintholeskia) being a misindentification of Neosolieria Townsend. Trochiloleskia was included in the synonymy of Eumyobia and Trochiloglossa in the synonymy of Sipholeskia. Three monotypic genera: Parthenoleskia, Tapajoleskia and Urumyobia Townsend were synonymized with Leskia, while Galapagosia, Geneodes and Metamyobia were synonymized with Stomatodexia. Besides the taxonomic changes this paper revises Eumyobia; Sipholeskia and Uruleskia, with the redescription of their species, including the type-species; description of four new species of Uruleskia from the north of Brazil: U. alba spec. nov., U. extremipilosa spec. nov., U. infima spec. nov. and U. parcapilosa spec. nov. and describes Murya gen.nov. for one new species Murya bicolor spec. nov. One new combination Sipholeskia tropica (Townsend) comb. nov. is proposed. Illustrations of the morphological characterers especially the male terminalia, keys to genera and species are also presented.